2020
DOI: 10.1088/1742-6596/1432/1/012059
|View full text |Cite
|
Sign up to set email alerts
|

Review of feasibility wind turbine technologies for highways energy harvesting

Abstract: Wind energy is one of the non-conventional forms of energy and it is available in affluence. It is also claimed that the wind power is pollution-free, replacement of fossil fuel and that its source of energy is freely available. Electricity can be generated with the help of a wind turbine generator. In this paper, a comprehensive study on contemporary portable wind energy harvesters has been conducted. The different existing performance such as reliability evaluation models, various problems related to structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…From vehicles transferring by air Pressure wave systems 5-500 μJ/single vehicle pass [30] 0.3% Air movement systems 1-500 J/single vehicle pass [31,32] 2.4%…”
Section: Road Energy Harvesting Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From vehicles transferring by air Pressure wave systems 5-500 μJ/single vehicle pass [30] 0.3% Air movement systems 1-500 J/single vehicle pass [31,32] 2.4%…”
Section: Road Energy Harvesting Methodsmentioning
confidence: 99%
“…The energy obtained in the model system from a single‐vehicle pass is of the order of one hundred joules. The current review of research on this subject can be found in the article [ 32 ] published in 2020. Works carried out in various research centers, turbine prototypes, results of CAD model, and CFD simulation tests as well as development prospects of this technology are discussed here.…”
Section: Harvesting Road Energy Transferring By Airmentioning
confidence: 99%
“…Wearable antennas are constructed using various dielectric and conductive materials chosen for their ability to withstand mechanical deformations such as twisting, bending, and wrapping while also providing protection from electromagnetic radiation. Fabric and non-fabric materials have been utilised to fabricate wearable antennas, but the proper characterisation of fabric materials is essential prior to use [66]. Textile materials, including felt cloth, polyester cotton, and cordura, are commonly used in wearable antennas for RF energy harvesting due to their widespread availability [67][68][69].…”
Section: Rf Wearable Energy Harvesting Antenna Designmentioning
confidence: 99%
“…Furthermore, ref. [66] conducted a feasibility review of wind turbine technology for highway energy harvesting. The aim was to utilise natural wind energy in the most effective manner to achieve maximum electric output.…”
Section: Power Managementmentioning
confidence: 99%
“…The vertical-axis wind turbine (VAWT) is one of the wind turbines that are used to harvest the wind energy from vehicles wake on highways. Liew et al (2020) and Uddin et al (2022) conducted a review to maximize the electric output by making the best use of the wind energy. To suggest a location for the vertical VAWT on the highway, the possibility of a small wind turbine is explored by Al-Aqel et al (2016).…”
Section: Introductionmentioning
confidence: 99%